Famae petitor. Lucan’s Portrayal of Pompey. - Pypłacz, Joanna (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2014)
In spite of the fact that Lucan’s sympathies are apparently with the Republicans, his attitude to Pompey, which emerges from the Pharsalia, turns out to be rather critical. Moreover, this criticism actually comes very close to ridicule. Lucan depicts Pompey as a senile and narcissistic leader who dwells on his past success and lives in the world of his own fantasies. Trapped in the vicious circle of his delusions of grandeur, he is rather grotesque than majestic. The harder he tries to enhance his public image, the more pathetic he becomes both in the eyes of his friends and in those of his enemies. The effects of his efforts are, therefore, quite contrary to their purpose. On the one hand, the figure of the senile and deluded Pompey is the caricature of the decaying Roman Republic, whose degeneracy it obviously mirrors. On the other hand, however, Lucan’s grotesque anti-hero is the exact opposite of archetypal epic characters such as Virgil’s Aeneas. Willing yet unable to emulate his literary predecessors, he functions as the caricature of the literary paradigm of a standard epic hero.